The Integration of Dynamic Assessment in L2 Classroom: How Students Perceive it? - Kusumaningrum, Widya Ratna; Ferri Karma, Prima (Vision: Journal for Language and Foreign Language Learning, 2018)
The present study focuses on the implementation of traditional diagnostic test for speaking skill in the form of an interview with no specific set of corrective procedure. However, it triggers more increasing worries on the significance of standardized test such as not being able to unlock students’ speaking potential. This study highlights on Dynamic Assessment (DA) based on the Vygotsky’s Sociocultural Theory (1978). Fundamentally, DA inserts mediation process such as prompts, hints, and leading questions in its interview process. This study compares the efficacy of Dynamic Assessment (DA) and the standardized diagnostic test/Non-Dynamic Assessment (NDA) in diagnosing and unlocking their potential. Using a quasi-experimental research with non-equivalent group design (NEGD), this study focused on four micro speaking skills including pronunciation, vocabulary, grammar, and fluency. The results suggested that the use of DA was able to identify their current speaking performance and uncover their speaking potential even if some were claimed to have the similar speaking level. While, the standardized test (NDA) emphasized only on the current performance and was not able to elicit their potential.